A unique clinical appearance of upper maxillary premolar associated with dentigerous cyst: case report / Mohd Faizal Abdullah ... [et al.] - Abdullah, Mohd Faizal; Abdul Rahman, Shaifulizan; Nik Abdul Ghani, Nik Rozainah; Mamat, Rosnani; Harun, Masitah Hayati (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
During dental development, a variety of hereditary and environmental variables interact to cause dental abnormalities. The etiology may involve multi-tiered, multi-directional, and multi-factorial processes. Fusion is a dental anomaly that happens during tooth development, where two separated teeth bud fuse together to form a single tooth. The morpho-differentiation or histo-differentiation stages of tooth development, genetic and environmental variables can induce developmental dental abnormalities. A clinical resemblance of a "double-headed" maxillary second upper left premolar with two crowns, formed on the both coronal and apical root end or whether it is just a hypercementosis of apical root discovered after surgical extraction and enucleation of cyst. Investigations to confirm such unique findings were performed. This case report discusses the importance of clinical, radiographic and laboratory investigations to confirm the unique appearance of the maxillary second premolar